THE EFFECT OF AB MIX FERTILIZER CONCENTRATION AND PLANTING MEDIA ON THE GROWTH AND YIELD OF PAKCOY (Brassica rapa L.) USING A HYDROPONIC WICK SYSTEM - Martalina, Savira Dwi; Widiwurjani, Widiwurjani; Suhardjono, Hadi (International Journal of Multidisciplinary Research and Literature, 2024)
Determining the concentration of nutrients and planting media in a hydroponic wick system is necessary to increase the growth and yield of Pakcoy mustard greens (Brassica rapa L.). The research used a Completely Randomized Factorial Design consisting of 2 factors. The first factor is the concentration of AB Mix fertilizer, which consists of 4 levels, namely 500 ppm, 1.000 ppm, 1.500 ppm, and 2.000 ppm. The second factor is the planting media, which consists of 2 levels: cocopeat planting media and husk charcoal. If the analysis result shows a significant difference, then continue with the BNT test at the 5% level. The research stated that applying 1.500 ppm AB Mix fertilizer and husk charcoal planting media could provide the best results in all parameters